Bet 2: Does intravenous vitamin C improve mortality in patients with severe sepsis?. Issue 4 (20th March 2018) - Sheikh, Mohammed; Horner, Daniel
Abstract : A shortcut review was carried out to establish whether the use of intravenous vitamin C can reduce mortality or morbidity in patients diagnosed in the early phases of severe sepsis. Three directly relevant papers were found using the reported search strategy. The author, date and country of publication; patient group studied; study type; relevant outcomes; results and study weaknesses of the best papers are tabulated. It is concluded that there is insufficient high-quality research to justify the routine use of vitamin C in severe sepsis. Further multicentre, double-blinded randomised controlled trials are required in order to establish the role of vitamin C in sepsis.